Improving the eNodeB Coverage of a Bad Spot Area by Using A Relay Node - Ni'mah, Fivie; Putri, Hasanah Putri (IJAIT (International Journal of Applied Information Technology), 2018)
The quality of LTE (Long Term Evolution) network in WR Supratman Street, Bandung is categorized as quite bad as shown by the average RSRP (Reference Signal Receive) and SINR (Signal to Interference Noise Ratio) values of -101.30 dBm and 2.43 dB, respectively. Both parameters are below the standard operator with the average RSRP and SINR standard values of -101.30 dBm and 2.43 dB, respectively. The previous field measurement indicated that the area belonged to a bad spot area caused by shadowing buildings. This study used the node scheme of decode and forward and physical mode of inband relay node with the aim of extending the eNodeB coverage. By applying this technique, the average RSRP value increased by 18% and the average SINR value increased by 53%. Based on the RF (Radio Frequency) parameters, the average RSRP value with samples below the -85 dBm standard improved by 81%, while the average SINR value with samples below 5 dB improved by 45%.